Adipose Tissue-Derived Mesenchymal Stem Cells as a New Host Cell in Latent Leishmaniasis - Allahverdiyev, Adil M.; Bagirova, Melahat; Elcicek, Serhat; Koc, Rabia Cakir; Baydar, Serap Yesilkir; Findikli, Necati; Oztel, Olga N. (Amer Soc Trop Med & Hygiene, 2011)
Some protozoan infections such as Toxoplasma, Cryptosporidium, and Plasmodium can be transmitted through stem cell transplantations. To our knowledge, so far, there is no study about transmission of Leishmania parasites in stem cell transplantation and interactions between parasites and stem cells in vitro. Therefore, the aim of this study was to investigate the interaction between different species of Leishmania parasites and adipose tissue-derived mesenchymal stem cells (ADMSCs). ADMSCs have been isolated, cultured, characterized, and infected with different species of Leishmania parasites (L. donovani, L. major, L. tropica, and L. infantum). Infectivity was examined by Giemsa staining, microculture, and polymerase chain reaction methods. As a result, infectivity of ADMSCs by Leishmania parasites has been determined for the first time in this study. According to our findings, it is very important that donors are screened for Leishmania parasites before stern cell transplantations in regions where leishmaniasis is endemic.
Keywords: American Cutaneous Leishmaniasis; Fragment-Length-Polymorphism; Polymerase-Chain-Reaction; Visceral Leishmaniasis; Adipogenic Differentiation; Microculture Method; Peripheral-Blood; Stromal Cells; Bone-Marrow; Diagnosis